1986
DOI: 10.1038/clpt.1986.198
|View full text |Cite
|
Sign up to set email alerts
|

Food effects on propranolol systemic and oral clearance: Support for a blood flow hypothesis

Abstract: The influence of a high-protein meal as compared to fasting on the disposition of simultaneous intravenous and oral doses of propranolol, as well as on indocyanine green clearance, was examined in six normal subjects. The intravenous dose (0.1 mg/kg) was unlabeled propranolol and the oral dose (80 mg) was a stereospecifically deuterium-labeled pseudoracemate of propranolol. Systemic clearance of propranolol increased 38%, from 1005 +/- 57 to 1384 +/- 115 ml/min (mean +/- SE; P less than 0.05) as a result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…However, the effect of food may be explained by the rate of gastric emptying, since food can delay gastric emptying, thereby increasing the available time for absorption. Food may also increase mesenteric blood flow and enhance absorption; this increased mesenteric blood flow might also cause decreased 'first pass' hepatic clearance by creating functional shunts in the liver [9]. To date, there is no information suggesting that MK-0476 is a 'high clearance' drug susceptible to this effect.…”
Section: Analysis Ofpharmacokinetic Datamentioning
confidence: 93%
“…However, the effect of food may be explained by the rate of gastric emptying, since food can delay gastric emptying, thereby increasing the available time for absorption. Food may also increase mesenteric blood flow and enhance absorption; this increased mesenteric blood flow might also cause decreased 'first pass' hepatic clearance by creating functional shunts in the liver [9]. To date, there is no information suggesting that MK-0476 is a 'high clearance' drug susceptible to this effect.…”
Section: Analysis Ofpharmacokinetic Datamentioning
confidence: 93%
“…The mechanism by which food increases the bioavailability of praziquantel remains to be demonstrated. The effect could be related to tablet disintegration, better drug dissolution, or other factors, such as changes in hepatic blood flow or in the metabolism of the drug during the first passage through the liver (5)(6)(7)(8). Considering that both treatments had a high carbohydrate content, it is possible that carbohydrates had the major influence on the bioavailability of praziquantel.…”
mentioning
confidence: 99%
“…The postprandial increase in systemic clearance of i.v. drugs having high hepatic clearance is well known and is mainly explained by an increased hepatic blood flow [19]. However, because the effect of food on hepatic blood flow was not assessed in the present trial, the PK model estimates the food effect on the clearance based on the observed concentration data.…”
Section: Pharmacokinetic/pharmacodynamic Modellingmentioning
confidence: 99%